Serious fish disease spreads across South East Asia - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1989)
A virus causing a new but serious disease of fish is spreading quickly across South East Asia. When the disease was first noticed in 1980 it was feared that the cause might be chemicals polluting the water. Now researchers from the Institute of...